Dimensions of international migration - Hoikkala, Päivi; Wills, Dorothy Davis (Cambridge Scholars Pub., 2011)
This text follows migrants from challenging situations in their homelands into even more challenging new worlds. The essays use post-colonial literature, ethnographic research, primary sources, interviews and a variety of other approaches to reveal the experiences of immigrants and their hosts.